Speech signal marking on the base of local magnitude and invariant segmentation - Rashkevych, Yu.; Peleshko, D.; Pelekh, I.; Izonin, I. (Publishing House of Lviv Polytechnic National University, 2014)
The paper suggests a new watermarking scheme based on invariantmethod of segmentation and the use of local magnitude for marking speech signals. The watermark is embedded in the chosen form at peaks with the spectrum magnitude of each nonoverlapping frame of audio signal.The suggested scheme of marking speech signals ensures the reliable protection against several types of attacks, i.e. noise, trimming, re-sampling, re-quantization, compression, and lower frequencies filtering. У роботi пропонується нова схема водяних знакiв на основi iнварiантного методу сегментацiї та використаннi локальних магнiтуд для маркерування мовних сигналiв. Водяний знак вбудовується в обраному видi у пiки з магнiтудою спектра кожного неперекриваючого кадру аудiосигналу. Запропонована схема маркерування мовних сигналiв забезпечує надiйнiсть вiд декiлькох видiв атак, таких, як шуму, обрiзки, повторної дискретизацiї, повторного квантування, стиснення i фiльтрацiї нижнiх частот.
Маркерування мовного сигналу на основi локальних магнiтуд та iнварiантної сегментацiї
Keywords: speech signal; marking; watermark; primary segmentation; symmetric matrix of distances; pseudoinverse matrix; Moore-Penrose algorithm; singular decomposition; Euclidean; Chebyshev and cosine metrics; similarity measure; мовний сигнал; маркерування; водяний знак; первинна сегментацiя; симетрична матрична вiдстаней; сингулярний розклад; псевдо обернена матриця; алгоритм Мура-Пенроуза; евклiдова, чебишевська та косинусна метрики; мiра подiбностi